RELIGIUOS MODERATION IN ISLAMIC EDUCATION WITH A NEW PARADIGM TRANSLATION OF TAFSIRIYAH MUHAMMAD THALIB - Zakiyah, Ermita (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The purpose of this study is to examine the paradigm of religious moderation in Islamic education with the new paradigm of Muhammad Thalib's translation of Tafsiriyah, the approach used in this study is Maudhui or thematic terms. Muhammad Talib's thoughts became the main source of the Al-Qur'an Tarjamah Tafsiriyah (Understanding the Meaning of the Qur'an is Easier, Precise and Enlightening), with the steps used to collect descriptive analytical library data by revealing the interpretation patterns of Muhammad Talib. Interpretation approach is an analysis of understanding interpretive thinking with Islamic moderation in comprehensive Islamic education. The results of this study are to provide an understanding of the interpretation of the Qur'an version of Muhammad Thalib on religious moderation in Islamic education as a new paradigm foothold to improve understanding of the verses of al-Qur'an. -Qur'an so that the Qur'an can be applied and radicalism in the name of religion by bringing the interpretation of the Qur'an can be eradicated through moderate Islamic education.